Catheter-Based Radiofrequency Renal Sympathetic Denervation Decreases Left Ventricular Hypertrophy in Hypertensive Dogs. (26th April 2021) - Tu, Shan; Shen, Zhi-Jie; Wang, Xiao-Yan; Zeng, Li-Xiong; Zhang, Zhi-Hui
Abstract : This study explored the effects of renal sympathetic denervation (RDN) on hyperlipidity-induced cardiac hypertrophy in beagle dogs. Sixty beagles were randomly assigned to the control group, RDN group, or sham-operated group. The control group was fed with a basal diet, while the other two groups were given a high-fat diet to induce model hypertension. The RDN group underwent an RDN procedure, and the sham-operated group underwent only renal arteriography. At 1, 3, and 6 months after the RDN procedure, the diastolic blood pressure (DBP) and systolic blood pressure (SBP) levels were markedly decreased in the RDN group relative to the sham group (P < 0.05 ). After 6 months, serum norepinephrine (NE) and angiotensin II (AngII), as well as left ventricular levels, in the RDN group were statistically lower than those in the sham group (P < 0.05 ). Also, the left ventricular mass (LVM) and left ventricular mass index (LVMI) were significantly decreased, while the E/A peak ratio was drastically elevated (P < 0.05 ). Pathological examination showed that the degree of left ventricular hypertrophy and fibrosis in the RDN group was statistically decreased relative to those of the sham group and that the collagen volume fraction (CVF) and perivascular circumferential collagen area (PVCA) were also significantly reduced (P < 0.05 ). Renal sympathetic denervation not only effectively reduced blood pressure levels in hypertensive dogs but also reduced left ventricular hypertrophy and myocardial fibrosis and improved left ventricular diastolic function. The underlying mechanisms may involve a reduction of NE and AngII levels in the circulation and myocardial tissues, which would lead to the delayed occurrence of left ventricular remodeling.